IMPACT OF A CANCER OF UNKNOWN PRIMARY (CUP) SERVICE ON END OF LIFE PLANNING FOR PATIENTS WITH METASTATIC DISEASE. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Marshall, Jackie; Stewart, James; Hancock, Louise; Gillmore, Roopinder
Abstract : Background: NICE recommends every cancer centre should establish a consultant-led CUP team (oncology, palliative care consultants and specialist nurse) (NICE CG 104). One of the aims of this service is to ensure patients with imaging suggestive of metastatic disease have early review by oncology and palliative careTable 1 . Aim: This analysis assessed the impact of a CUP service on patients diagnosed with metastatic cancer who were not fit enough for active treatment. Methods: Clinical notes were reviewed for all acute hospital admissions with an imaging-based diagnosis of metastatic cancer, who did not go onto receive active treatment. A retrospective analysis performed prior to the establishment of the CUP team (January-April 2009), was compared to prospective data following the launch of the CUP service (June-December 2012). Results: Following establishment of the CUP team – mean length of stay was significantly reduced (6.7 days, 18.6 days, p<0.004) and only one patient was unable to be discharged to their preferred place of death. Furthermore all patients were reviewed by palliative care to optimise symptom control (Table 1 ). Conclusions: Early assessment by the CUP service facilitates specialist input from oncology and palliative care, successful discharge planning, with reduced length of stay and rates of readmission.